National Marrow Donor Program–Sponsored Multicenter, Phase II Trial of HLA-Mismatched Unrelated Donor Bone Marrow Transplantation Using Post-Transplant Cyclophosphamide. Issue 18 (20th June 2021) - Shaw, Bronwen E.; Jimenez-Jimenez, Antonio Martin; Burns, Linda J.; Logan, Brent R.; Khimani, Farhad; Shaffer, Brian C.; Shah, Nirav N.; Mussetter, Alisha; Tang, Xiao-Ying; McCarty, John M.; Alavi, Asif; Farhadfar, Nosha; et al.
Abstract : PURPOSE: Hematopoietic cell transplantation (HCT) is curative for hematologic disorders, but outcomes are historically inferior when using HLA-mismatched donors. Despite unrelated donor registries listing > 38 million volunteers, 25%-80% of US patients lack an HLA-matched unrelated donor, with significant disparity across ethnic groups. We hypothesized that HCT with a mismatched unrelated donor (MMUD) using post-transplant cyclophosphamide (PTCy), a novel strategy successful in overcoming genetic disparity using mismatched related donors, would be feasible and increase access to HCT. PATIENTS AND METHODS: We performed a prospective phase II study of MMUD bone marrow HCT with PTCy for patients with hematologic malignancies. The primary end point was 1-year overall survival (OS), hypothesized to be 65% or better. 80 patients enrolled at 11 US transplant centers (December 2016-March 2019). Following myeloablative or reduced-intensity conditioning–based HCT, patients received PTCy on days +3, +4, with sirolimus and mycophenolate mofetil starting on day +5. We compared outcomes to Center for International Blood and Marrow Transplant Research contemporary controls receiving PTCy. RESULTS: Notably, 48% of patients enrolled were ethnic minorities. 39% of pairs were matched for 4-6 out of 8 HLA alleles. The primary end point was met, with 1-year OS of 76% (90% CI, 67.3 to 83.3) in the entire cohort, and 72% and 79% in the myeloablative and reduced-intensity conditioning strata, respectively. Secondary end points related to engraftment and graft-versus-host-disease were reached. Multivariate analysis comparing the study group with other mismatched HCT controls found no significant differences in OS. CONCLUSION: Our prospective study demonstrates the feasibility and effectiveness of HCT with an MMUD in the setting of PTCy. Remarkably, nearly half of the study participants belonged to an ethnic minority population, suggesting this approach may significantly expand access to HCT.